I have the differential equation:

$$\frac{\partial C}{\partial t} = D \frac{\partial^2 C}{\partial z^2}$$

to solve it, the author of my book carries out the following replacement:

$$-2\zeta \frac{dX}{d \zeta} = \frac{d^2 X}{d \zeta^2}$$

with $X=1-\frac{C}{C_S}$ and $\zeta =\frac{z}{(4Dt)^{1/2}}$.

How can I prove that the last equation is identical to the first in Mathematica?

Thank you so much for your time.

  • $\begingroup$ Could you please describe the substitution z->zeta in detail? What means Dt? $\endgroup$ Jan 5 '18 at 11:12
  • $\begingroup$ Hello @UlrichNeumann, D is a constant, z and t are variables. $\endgroup$ Jan 5 '18 at 11:35


pde = Derivative[1, 0][C][t, z] == d Derivative[0, 2][C][t, z]

Simplify[pde /. C -> Function[{t, z}, CS (1 - X[z/Sqrt[4 d t]])] /.z -> \[Zeta] Sqrt[4 d t] ]   
(* (CS (2 \[Zeta] Derivative[1][X][\[Zeta]] + (
X^\[Prime]\[Prime])[\[Zeta]]))/t == 0 *)

which confirms the replacement!

  • $\begingroup$ Your solution is extremely clear @UlrichNeumann! $\endgroup$ Jan 6 '18 at 7:14

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.